Tourism : an introduction - Youell, Ray. (Harlow, Essex : Addison Wesley Longman, 1998)
Tourism - the world's biggest industry. Structure and organisation of the International tourism industry. European tourism. Tourism in the United Kingdom...
Keywords: Tourism; Tourism